Analyses of Curupira Block Cipher - Nakahara Jr, Jorge (Anais do Simpósio Brasileiro de Cibersegurança (SBSeg), 2008)
Curupira is a 96-bit block cipher, with keys of 96, 144 or 192 bits, and variable number of rounds, an algorithm described at SBRC 2007. This paper presents impossible-differential, boomerang and higher-order multiset attacks on reduced-round versions of Curupira, that were not previously considered in the security analysis by its designers. Also, we provide security analyses based solely on the block size and on the key size of the cipher, such as plaintext leakage and related-key attacks. Our analyses indicate new attacks on up to 6-round Curupira.